Factors Affecting Consumer Satisfaction - Girsang, Nanda March Dhearni; Faadhil, Faadhil (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This study presents a literature review of the factors influencing consumer satisfaction. Consumer satisfaction results from the accumulation of consumers and consumers where there is an assessment of the unique features of the product or service that are by consumer expectations. Satisfying consumer needs is the desire of every company. In addition to being an essential factor for the company's survival, satisfying consumer needs can increase competitive advantage. The importance of studying consumer satisfaction has been widely expressed in previous studies. The study revealed many factors influencing consumer satisfaction, such as product quality, service quality, price, warranty, and emotional and perceived security. The research method uses a systematic literature review. Research data was obtained through an internet search regarding consumer satisfaction journals with the criteria for articles used, namely those published in the last 5 years, from 2019 to 2024. Article searches through the Researchgate database, Google Scholar and Google Search were done using the keywords satisfaction, consumers, and customers. The number of journals analyzed was 11 journals. Data is used to identify and analyze factors that influence consumer satisfaction. The results of this study conclude that several factors affect consumer satisfaction, including duct quality, service quality, price, warranty, emotion, and perception of security.